Working from home and management controls - Konstantin Flassak; Julia Haag; Christian Hofmann; Christopher Lechner; Nina Schwaiger; Rafael Zacherl (Journal of Business Economics, 2022)
The Covid-19 pandemic and the corresponding shift toward working from home (WFH) amplifies control problems within organizations and poses severe challenges for management control as employees' tasks are difficult to observe under WFH conditions. We examine the association between WFH and action controls. Based on a survey among employees in a large international corporation, we find that under WFH conditions the organization more intensively uses standardization and planning participation. We also examine the association between WFH and employee outcomes. The findings suggest that WFH is associated with more time employees spend in meetings and a higher job focus. Overall, the study adds to the literature by exploring the association between WFH and the use of management controls in organizations.
Keywords: M12; M41; M54; 650; Covid-19 pandemic; Working from home; Management control; Employee outcomes